Cten promotes epithelial-mesenchymal transition through post-transcriptional stabilization of Snail - Thorpe, Hannah; Asiri, Abdulaziz; Akhlaq, Maham; Ilyas, Mohammad (Wiley, 2017)
Cten promotes cell migration however the knowledge of underlying signalling pathways is sparse. We have shown that Cten downregulates E-cadherin, a feature of epithelial to mesenchymal transition (EMT). This prompted us to investigate whether Cten further contributed to EMT processes to regulate cell motility.